Memrise As A Builder Students Vocabulary - Affandi, Muhammad Hasan; Syafi’i, Ahmad (Efektor, 2018)
Memrise is a platform online learning to learn about new languages in the world. It will help the people especially for students to improve their foreign languages. especially in English language. There are so many features that it could help the students being happy to learn about new languages. Nowadays, In the millennial era or twenty first century, most people have their own gadget. Therefore, people must be mastering the high technology to support their daily life and get the many informations instantly and accurately. Then, it must be mastered by students because if the students can use gadget wisely, it will help and support their education and get big change to read world news a lot. That is way, not only students but alsoall of people’s levels in the world must use the high technology wisely to help and support their necessary better because it will develop the human being capacity to adapt with their environment.